Characterization of microorganisms with probiotic potential isolated from Brahman calf manure in Sucre, Colombia - Castillo Arroyo, Pedro Luis (2018)
The objective of the study was to characterize microorganisms with probiotic potential of manure of lactating Brahman calves in Sucre (Colombia). Bacteria and yeasts were isolated from manure samples and the probiotic capacity of these strains was determined by bile salt resistance test (0.05, 0.1, 0.15, 0.3%), resistance to acidic pH (pH 3, 4, 5.6, 7 ), tolerance to NaCl (2, 4, 6, 8, 10%) and antagonistic activity (Salmonella sp and Escherichia coli). Nine microorganisms were identified and three passed the tolerance tests. The antagonistic capacity was determined against pathogenic bacteria (Salmonella sp and E. coli), evidenced by halos (mm) of the three selected strains. The identification of the strains was carried out by the biochemical methods API 50 CHL V5.1 for Lactobacillus and API 20 AUX for yeasts. Molecular analysis of two strains (M13a and 103M2) identified strain M13a as Enterococcus faecium and strain 103M2 as Candida krusei. In conclusion, Enterococcus faecium becomes a viable alternative for the formulation of a biopreparation to improve the productive parameters and decrease gastrointestinal disorders in lactating calves.